A macro projection of China's Hospital Workforce requirements based on determined significant factors - Zhang Ming.
In China, not enough attention is given to the planning of human resources for health by the Ministry of Health. A search for an effective and feasible method of health workforce projection considering the factors that influence macro planningin on going.This research aims to determine China's hospital workforce requirement for the year 2013 using an appropriate method and approach based on the determined significant factors.The study design utilizes a combination of qualitative methods and operational research. Both primary and secondary data are employed. The study population consists of the current hospital workforce in the sampling areas of the Survey of National Health Services (SNHS) in relation to the current and projected population of China.Significant factors which greatly affect the hospital workforce requirement were identified by the Delphi technique in terms of the generic factors and substantial factors. The technical panel meeting assessed the generic methods recommended by the WHO with certain criteria, and effective and feasible method was determined for the projection. As an operational research, a tentative projection was made for determining the China's hospital workplace requirement for the year 2013. The focus group discussions were used to validate the results of the tentative projection.This study shows that the significant factors which greatly affect China's hospital workforce requirements are the hospital service demand, population, internal administration, and health policies. The WHO projection model combined with other qualitative methods such as Focus Group Discussions and Delphi technique proved to be the effective method for the macro projection of the China's hospital workforce requirements. Currently, China's hospital workforce is seriously maldistributed in the urban area and wealthy rural area, and are too numerous in most hospitals.The following are recommended to enhance the macro planning of hospital workforce as well as health workforce in China to promote the utilizatio of hospital services: (1) to determine more substantial factors relevant with the determined significant factors as the independent variables for the projection; (2) to accomplish follow-up studies on the five typical areas of SNHS; (3) to develop more appropriate methods for determining the key indicators of the hospital workforce requirement and hospital services demand; (4) to set priorities for improvement of hospital performance efficienc; (5) to establish and complete the development of hospital licensing procedures and health professional licensure examinations; (6) to complete the procedure of hospital classification; and (7) to develop a comprehensive projection model based on the research for addressing the local condition of China.
Thesis (MHA)--University of the Philippines Manila, 1999
Keywords: Health Personnel -- China